FORMATION OF COGNITIVE METAPHORS IN COMMERCIAL TEXTS AND THEIR CULTURAL FOUNDATIONS - Xolisova Gavharoy Mannobjon qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: The formation of cognitive metaphors in Uzbek commercial discourse is directly linked to the national linguistic picture of the world and cultural codes, serving to activate positive cognitive associations in the consumer's mind. The construction of cognitive metaphors in commercial texts primarily relies on several core models, one of the most prominent being the "Product — Human" (Anthropomorphism) model.